Mutu Sosis Lele Dumbo (Claris garipinus) Akibat Penambahan Jenis dan Konsentrasi Binder - Widjanarko, Simon B.; Martati, Erryana; Nouvellia, Pritta (Jurnal Teknologi Pertanian, 2004)
This paper reported physico-chemical dan sensory properties of cat fish sausages from different types of formula made by different types and concentrations of binder agents. Factorial Randomized Block Design with types and concentrations of binder (skim milk, egg white and soybean flour at 3, 5 and 7 %) was used in this experiment. Each treatments were replicated 3 times. The results showed that best treatment, which was, adding skim milk at 5%, has moisture content 69,77%, protein 49,03%, fat 13,88%, texture 0,0961 mm/g/sec; WHC 54,51%, emulsion stability 98,64%. Sensories determination showed that color score was 4,90; food texture 5,00 and taste 5,40 and this sensories attributes were considered to be more likely acceptable . There was significantly different between this best treatment and controlled on its moisture content, protein, fat, food texture, WHC and emulsion stability, whereas there was significantly differention on food texture based on sensoriy studies, but color and taste were not significantly different. Â  Key Words :Â  cat fish, sausage, binder agent